2006
DOI: 10.1128/iai.00025-06
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of a Family of Transmembrane Kinases from the Protozoan Parasite Entamoeba histolytica

Abstract: The signaling proteome of Entamoeba histolytica is made of transmembrane kinases (TMKs) that are rarely found in unicellular eukaryotes. There are 90 TMK genes reported for E. histolytica, and these have been grouped into nine distinct families based on motifs present on both extracellular and kinase domains. Of these, the B1 family was chosen for further analysis. Genomic sequencing revealed the presence of 28 members belonging to this family. Genes corresponding to the majority of these were truncated and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Expression of PaTMK and sub-family B 1 TMKs has been examined at the protein level (Mehra et al, 2006; Boettner et al, 2008) however studies have been limited to Western blotting and microscopy. Consequently, it is unknown whether TMKs are heterogeneously expressed by trophozoites within a population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of PaTMK and sub-family B 1 TMKs has been examined at the protein level (Mehra et al, 2006; Boettner et al, 2008) however studies have been limited to Western blotting and microscopy. Consequently, it is unknown whether TMKs are heterogeneously expressed by trophozoites within a population.…”
Section: Resultsmentioning
confidence: 99%
“…When the TMKs were divided into nine sub-groups (A, B 1–3 , C, D 1–2 , E and F) based on signature motifs found within the substrate recognition regions of their kinase domains, similarity in the extracellular domains became apparent within sub-groups with respect to the size and the distribution of cysteine-rich motifs, suggesting that TMK subgroups represent functionally distinct receptor families with sub-family-specific substrates and ligands (Beck et al, 2005). However, only two TMKs have been partially characterized to date: PaTMK (TMK96, Subfamily B 3 ) is expressed at the cell surface and functions in erythrophagocytosis (Boettner et al, 2008) and members of the B 1 family of TMKs play a role in proliferation and sensitivity to serum-derived growth factors (Mehra et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…These have been categorized into nine families and a few have been functionally characterized. Members of EhTMKB1 family, such as EhTMKB1-9 and EhTMKB1-2, have been shown to be involved in cellular proliferation and serum response [74,75]. PATMK (EhTMKB3-96) co-localized with human erythroc yt e s at th e s i t e o f co nt ac t a n d i s i nv ol ve d i n erythrophagocytosis and was identified during screening for proteins involved in the recognition and ingestion of apoptotic cells [76•].…”
Section: Cell Surface Molecules Of E Histolyticamentioning
confidence: 99%
“…These studies have shown the role of this family in serum responsiveness and proliferation. While TMKB1-3 is constitutively expressed at a low level, the expression of TMKB1-9 appears to be regulated by serum, being low in serumstarved cells and induced to high levels after the addition of serum [73,74]. In fact, TMKB1-9 is the major TMKB1 family member to be expressed (ca.…”
Section: Receptor Kinasesmentioning
confidence: 99%
“…The automatic curation was performed by Gblock and tree building by PhyML. The significant bootstrap values above 50% are shown[74].…”
mentioning
confidence: 99%